Rapid resolution of pulmonary Langerhans cell histiocytosis. (6th June 2013) - Chong, Sy Giin; Samaha, Mario; Samaha, Georges; Casserly, Brian
Abstract : A 38-year-old woman with a long-term history of smoking presented to the lung cancer clinic with weight loss and recurrent lower respiratory tract infections. A diagnosis of Langerhans cell histiocytosis was made by specimen samples taken from video-assisted thoracoscopic surgery.  She was advised to stop smoking, which she adhered to. She was followed up in the respiratory clinic with pulmonary function tests every 6 months, which were all normal. Follow-up chest x-ray showed complete resolution of the multifocal interstitial infiltrates, and with smoking cessation, the patient has sustained an excellent quality of life.